Business System Analysis Based On Multi Level Marketing In The Perspective of Islami Business Ethics (Case Study: PT. Veritra Sentosa International) - Achmad Fajaruddin; Bella Tahya Hania (University of Darussalam Gontor, 2018)
Nowadays, have came varieties of online application that can be used to make an online payment, one of it is Paytren. The application launched by Treni is applying MLM system in it's business. Nowadays, has come a lot of MLM companies that deviated from the business ethics. While in Islam, the application of Islamic business ethics is mandatory. This research aims to know the business system based on MLM and how the perspective of Islamic business ethics with the business that run by Treni. This research is a fi eld research with qualitative methods. Research data obtained from primary and secondary data. While primary data collected from interviews, observation and documentation. And secondary data collected from books, journals and other source that has same relation with the research. The conclusion are, the company is some company which sell a license for using an aplication with the aim for payying the daily needs and the montly bills, this aplication can be used in every kind of smartphone, especially in android and iOS. The partners get their commission from the selling of license to the other partners or from the transaction which done by their ownselves of by their downline. So for the implementation of Islamic business ethics, then Paytren has implemented an Islamic business ethics in it's business. It's known by the applied of the basic values of Islamic business ethics, namely Tawheed, khilafah, worship, tazkiyah and ihsan.